Reducing Information Gap and Increasing Market Orientation in the Agribusiness Sector: Some Evidences from Apulia Region - Contò, Francesco; Santini, Cristina; La Sala, Piermichele; Fiore, Mariantonietta (Recent Patents on Food, Nutrition & Agriculture, 2016)
Background: Market orientation plays a crucial role in reinforcing firm’s competitive advantage; nevertheless, marketing myopia can negatively affect a clear perception of the market. Methods: An organization that defines itself by product rather than by market terms is probably affected by marketing myopia, a narrowness of mind towards any newness – newness respect to firms’ convincement and routines - coming from the external environment. In that context some scientific relevant developments that comes from recent patents have been considered. This paper explores the determinants of marketing myopia in the Apulia wine business (South Italy). Results: The aim of this paper is to describe how experiential research based on Consumer Science research tools, can facilitate a better market knowledge. Experimental sessions carried out in 2013 in Apulia with a group of professionals from the oil and wine sectors clearly demonstrate how country of origin effect can improve marketing myopia. Conclusion: Through a protocol based on an “academicians - practitioners” model, professionals can be facilitated in their strategy formulation.
Keywords: market orientation